2018
DOI: 10.1111/apha.13190
|View full text |Cite
|
Sign up to set email alerts
|

Klotho protein supplementation reduces blood pressure and renal hypertrophy in db/db mice, a model of type 2 diabetes

Abstract: Aims: Klotho interacts with various membrane proteins, such as receptors for transforming growth factor (TGF)-β and insulin-like growth factor (IGF), to alter their function. Renal expression of klotho is diminished in diabetes. The present study examined whether exogenous klotho protein supplementation ameliorates kidney injury and renin–angiotensin system (RAS) in db/db mice. Methods: We investigated the effects of klotho supplementation on diabetic kidney injury and RAS. Recombinant human klotho protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 47 publications
2
49
0
1
Order By: Relevance
“…Patients with CKD exhibit significantly low levels of serum Klotho (Koh et al, 2001;Nitta et al, 2014), which is associated with hypertension in humans (Zhou et al, 2015) and mice (Takenaka et al, 2019). Although studies have yet to confirm whether patients with CKD Most of the FGF23-immunoreactive neurons also exhibited FGFR1-immunoreactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with CKD exhibit significantly low levels of serum Klotho (Koh et al, 2001;Nitta et al, 2014), which is associated with hypertension in humans (Zhou et al, 2015) and mice (Takenaka et al, 2019). Although studies have yet to confirm whether patients with CKD Most of the FGF23-immunoreactive neurons also exhibited FGFR1-immunoreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Klotho (1014 amino acids; molecular weight, 130 kDa), which is mainly produced in the distal convoluted tubules of the kidneys, parathyroid glands, and choroid plexus of the brain, is known as an anti-aging and anti-inflammatory protein (Clinton et al, 2013;Kuro-o, 2008;Kurosu et al, 2005). A previous study demonstrated that Klotho supplementation reduces blood pressure (BP) (Takenaka et al, 2019), while another study indicated that Klotho normalizes BP by depressing renin-angiotensin system protein (renin, angiotensin-converting enzyme and angiotensin II type1 receptor) in the kidneys (Zhou et al, 2015). Hypertension often occurs in patients with chronic kidney disease (CKD) (Campese, 1997), among whom serum Klotho levels are significantly decreased (Koh et al, 2001;Nitta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, upregulated Klotho levels inhibit inflammation by suppressing nuclear factor- κ B-mediated inflammatory processes in in vivo and in vitro studies [34, 35]. Additionally, sKlotho supplementation reduces renal angiotensinogen and angiotensin II levels, followed by the amelioration of renal fibrosis in diabetic and adriamycin nephropathy [36, 37]. Moreover, sKlotho therapy suppresses renal fibrosis by targeting several fibrotic signaling pathways, including TGF β -1/Smads and WNT/ β -catenin signaling [3739].…”
Section: Discussionmentioning
confidence: 99%
“…Takenaka et al detected elevated angiotensin II levels and angiotensinogen expression in diabetic mice affecting eg glomerular filtration rate (GFR) and albuminuria. These elevated values could be lowered with klotho protein supplementation, 16 a protein whose expression is reduced in type 2 diabetic rats 17 . Another approach is based on RAS‐associated Angiotensin (1‐7) peptide.…”
mentioning
confidence: 99%